Therapeutic efficacy of Ac-DMQD-CHO, a caspase 3 inhibitor, for rat spinal cord injury - (:unkn) unknown (ELSEVIER SCI LTD, 2008)
We investigated the therapeutic efficacy of Ac-DMQD-CHO, a caspase-3 inhibitor, and functional recovery in spinal cord injury in a rat model. Thirty rats were randomized into three groups of 10 each. In groups 2 and 3, spinal cord trauma was produced in the thoracic region. Group 3 rats were treated with Ac-DMQD-CHO. Treatment responses were evaluated based on histopathological and TUNEL staining findings at 24 h and 5 days post-injury. Neurologic performance was assessed during and following treatment. Twenty-four hours after injury, light microscopy examination revealed diffuse hemorrhagic necrosis, edema, vascular thrombi, and polymorphonuclear leukocyte infiltration in group 2 and 3 rats, but cavitation and demyelinization were less prominent in group 3. At this time point, treatment of the rats with Ac-DMQD-CHO significantly reduced the number of apoptotic cells. Traumatic injury to the spinal cord causes apoptosis and administration of Ac-DMQD-CHO decreases apoptosis and improves functional outcome. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: apoptosis; Ac-DMQD-CHO; caspase; caspase-3 inhibitor; programmed cell death; spinal cord injury; DELAYED NEURONAL DEATH; CELL-DEATH; APOPTOSIS; ACTIVATION; EXPRESSION; INDUCTION; ISCHEMIA; PROTEASE; MODEL